Active biopolymer film based on carboxymethyl cellulose and ascorbic acid for food preservation - Al Luqman Abdul Halim (N/A, 2017)
Active biopolymer film based on carboxymethyl cellulose and ascorbic acid for food preservation by Al Luqman Abdul Halim